Inflammation and platelet reactivity during adjunctive colchicine versus aspirin in patients with acute coronary syndrome treated with potent P2Y12 inhibitor - Lee, Seung-Yul; Cho, Jae Young; Gorog, Diana A.; Angiolillo, Dominick J.; Yun, Kyeong Ho; Ahn, Jong-Hwa; Koh, Jin-Sin; Park, Yongwhi; Hwang, Seok-Jae; Hwang, Jin-Yong; Kim, Jin Won; Jang, Yangsoo; et al. (Frontiers in Medicine, 2024)
Background In patients undergoing percutaneous coronary intervention (PCI), the use of anti-inflammatory therapy with colchicine is associated with a reduction of recurrent ischemic events. The mechanisms of such findings are not fully elucidated. Objectives To investigate the effects of colchicine versus aspirin on inflammation and platelet reactivity in patients with acute coronary syndrome (ACS) undergoing PCI. Methods This observational study compared laboratory measurements in ACS patients receiving single antiplatelet therapy with ticagrelor or prasugrel plus colchicine (MACT) (n = 185) versus conventional dual-antiplatelet therapy (DAPT) with aspirin plus ticagrelor or prasugrel (n = 497). The primary outcome was the frequency of high residual inflammation, defined as high-sensitivity C-reactive protein (hs-CRP) ≥2 mg/L at 1 month post-PCI. Multiple sensitivity analyses were performed for the primary outcome, including multivariable adjustment, propensity-score matching, and inverse-probability weighted methods. Results One month after PCI, patients treated with MACT had significantly lower levels of hs-CRP compared to those treated with DAPT (0.6 [0.4–1.2] vs. 0.9 [0.6–2.3] mg/L, p < 0.001). The frequency of high residual inflammation was also lower in the MACT group (10.8% vs. 27.2%, p < 0.001) (odds ratio [95% confidence interval] = 0.33 [0.20–0.54], p < 0.001). This effect was consistent across sensitivity analyses. There was no difference in platelet reactivity between MACT and DAPT (49.6 ± 49.0 vs. 51.5 ± 66.4 P2Y12 reaction unit [PRU] measured by VerifyNow, p = 0.776). Conclusion In ACS patients undergoing PCI, MACT was associated with a lower rate of high residual inflammation without increasing platelet reactivity compared to conventional DAPT. Clinical trial registration NCT04949516 for MACT pilot trial and NCT04650529 for Gyeongsang National University Hospital registry.